Composition effects of government expenditure on private consumption and output growth in Nigeria: A single-equation error correction modelling - Matthew Abiodun Dada (Romanian Journal of Fiscal Policy (RJFP), 2013)
This study examined the composition effect of government expenditure on private consumption and output growth in Nigeria using the framework of single equation error correction mechanism. The unit root and cointegration tests were conducted on the variables of interest while single equations Error Correction Models were estimated. The result suggests that government expenditures have long-run effect both on private consumption and output. The findings also revealed that government spending on education and health and social security have crowding-in effect on private consumption while other components such as government spending on administration, construction, agriculture, transport and communication have crowding-out effect on private consumption. The short-run behaviour of the model as captured by the ECM in the private consumption equation is that variables did not return to equilibrium after a short-run deviation. The finding also revealed that government spending on education and health, social security, agriculture and administration has positive effect on output while expenditure components such as government spending on construction, transport and communication have negative effect on output. The short-run behaviour of the model as captured by the ECM in the output equation is that variables did not return to equilibrium after a short-run deviation. The study also found that only two of the six components significantly influenced private consumption and output growth. The study therefore concluded that government spending on education and health, social security, agriculture and administration were growth-enhancing while government expenditure on construction, transport and communication were growth-retarding during the period under investigation.
Keywords: C22; E62; O23; H5; 330; Output growth; government spending; composition effect; long-run effect; cointegration